2011
DOI: 10.1029/2010gl045894
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oceanic heat variability on sea ice anomalies in the Nordic Seas

Abstract: [1] A strong control of sea ice area (SIA) in the Nordic Seas in the period 1982-2006 by oceanic heat variability is reported. In particular, variability of summer Atlantic water temperature in the Barents Sea Opening explains about 75% of the variance of the following winter SIA anomalies which opens prospects for seasonal predictability of regional sea ice cover. A strong link of winter SIA anomalies to variability in the previous spring sea surface temperature on the western (Greenland Sea) and eastern (Bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
93
2
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(110 citation statements)
references
References 23 publications
14
93
2
1
Order By: Relevance
“…In addition to the already mentioned Arctic sea ice or freshwater export role (Griffies and Bryan 1997;Koenigk et al 2006;Koenigk and Mikolajewicz 2009), Atlantic water temperature and salinity anomalies advection might be a significant source of predictability of the sea ice cover in this region, as suggested by Schlichtholz (2011). In the GIN Seas, the reemergence of oceanic anomalies due to the proximity of the deep water formation zone might also play an important role in sea ice cover variability and predictability (Roach et al 1993;Bitz et al 2005;Schlichtholz 2011). Finally, the correlation found by Koenigk et al (2012) between the sea ice cover in the GIN and Labrador Seas and the MOC suggests an influence of the large scale oceanic circulation as well.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In addition to the already mentioned Arctic sea ice or freshwater export role (Griffies and Bryan 1997;Koenigk et al 2006;Koenigk and Mikolajewicz 2009), Atlantic water temperature and salinity anomalies advection might be a significant source of predictability of the sea ice cover in this region, as suggested by Schlichtholz (2011). In the GIN Seas, the reemergence of oceanic anomalies due to the proximity of the deep water formation zone might also play an important role in sea ice cover variability and predictability (Roach et al 1993;Bitz et al 2005;Schlichtholz 2011). Finally, the correlation found by Koenigk et al (2012) between the sea ice cover in the GIN and Labrador Seas and the MOC suggests an influence of the large scale oceanic circulation as well.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, local air temperature and wind patterns also play a discernible role in determining sea-ice conditions in the northern Barents Sea and in the areas around Svalbard (Schauer et al 2002;Abrahamsen et al 2006;Dmitrenko et al 2009). In particular, local winds can redistribute the sea ice, changing its concentration and affecting ice fluxes from the northeast via the Transpolar Drift system, leading to significant changes in the area to the north of Svalbard (Å dlandsvik and Loeng 1991;Ingvaldsen et al 2004;Schlichtholz 2011). This area is also characterized by large interannual and decal variability with respect to sea-ice extent (Vinje 1999) and the overall decline in both sea-ice concentration and sea-ice extent in the Arctic since 1979 are widely documented (e.g., Parkinson and Cavalieri 2008;Comiso et al 2008;Comiso 2012).…”
Section: Upwellingmentioning
confidence: 99%
“…These are areas where the inflowing AW with temperatures T ∼ 5 • C occupies the surface layer, directly affecting the ocean-sea-ice-atmosphere interface (Sirevaag and Fer, 2009;Årthun et al, 2012;Ivanov et al, 2012). Over the last decades, observations indicate an increase of AW transport into the Arctic through the Barents Sea (e.g., Skagseth et al, 2008), which impacts the observed sea ice reduction (e.g., Schlichtholz, 2011;Årthun et al, 2012). The AW transport into the Arctic through the Fram Strait shows similar patterns and impacts (e.g., Ivanov et al, 2012;Alexeev et al, 2013).…”
Section: Introductionmentioning
confidence: 99%